An unusual presentation of osteoblastoma - Teixeira, Victor Perez; Assunçao Júnior, José Narciso Rosa; Oliveira, Letícia Almeida; Cadavid, Ana Maria Hoyos; Lemos Júnior, Celso Augusto; Sousa Júnior, Joao Alberto Lopes (Journal of Oral Diagnosis, 2017)
Osteoblastoma is a rare benign bone tumor that accounts for less than 1% of all primary bone tumors. Due to a low occurrence and varied histopathological aspects, this pathology becomes a diagnostic challenge. Therefore, our objective of reporting a case of osteoblas- toma in the maxilla is to discuss another presentation of this tumor. Male patient, suffering from leucoderma, 50 years old, presented an expansion in right superior vestibular groove with pain during palpation and an extensive osteolytic lesion in the right maxilla, of solid content, observed in computed tomography. With an anatomopathological diagnosis of osteoblastoma by an incisional biopsy, conservative surgery was performed to remove the lesion. The definitive analysis of the excised tumor confirmed the preoperative diagnosis. The patient has been followed up for a period of 5 years without relapses of the neoplasia. Therefore, due to the rarity and the difficult diagnosis, describing cases like this one and their presentation characteristics is extremely important to enhance knowledge of this pathology among professionals in the area of diagnosis and maxillofacial surgery.